Bacterial pathogen gene regulation: a DNA-structure-centred view of a protein-dominated domain - Dorman, Charles J.; Colgan, Aoife; Dorman, Matthew J. (Clinical science (1979), 2016)
The mechanisms used by bacterial pathogens to regulate the expression of their genes, especially their virulence genes, have been the subject of intense investigation for several decades. Whole genome sequencing projects, together with more targeted studies, have identified hundreds of DNA-binding proteins that contribute to the patterns of gene expression observed during infection as well as providing important insights into the nature of the gene products whose expression is being controlled by these proteins. Themes that have emerged include the importance of horizontal gene transfer to the evolution of pathogens, the need to impose regulatory discipline upon these imported genes and the important roles played by factors normally associated with the organization of genome architecture as regulatory principles in the control of virulence gene expression. Among these architectural elements is the structure of DNA itself, its variable nature at a topological rather than just at a base-sequence level and its ability to play an active (as well as a passive) part in the gene regulation process.